CASE REPORT : FISH BONE CORPAL IN ESOPHAGUS - Adilla Afra Amri; Fahrizal Fahrizal (Jurnal Kedokteran Diponegoro, 2023)
Esophageal foreign bodies are sharp or blunt objects or food that gets stuck and wedged in the esophagus due to being swallowed either intentionally or accidentally.A 53-year-old male patient arrived complaining of constant, worsening swallowing pain that has persisted for the past four days. The discomfort was initially experienced above the throat, but after attempting several traditional procedures to remove the bones, the pain was felt to shift to the region below the throat. Before going to the hospital, Patient has a history of consuming tuna bones. A fishbone was found in the esophagus area after an esophagoscopy was done.